An Overview of the Molecular Methods in the Diagnosis of Gastrointestinal Infectious Diseases. (24th March 2020) - Amjad, Muhammad
Abstract : Gastrointestinal infectious diseases are very common worldwide and an important cause of morbidity and mortality, particularly in infants in developing countries. Diarrhea and other intestinal infections are caused by a wide range of bacteria, viruses, protozoa, and parasites. Conventional diagnosis of these infections is performed by culture, microscopy, and antigen detection immunoassays. The traditional culture and microscopy procedures are time-consuming, lack sensitivity, and require special laboratory setup and well-trained staff. However, based on the advancement in the molecular diagnostics and with the introduction of commercially available tests, traditional diagnostic techniques have been continuously replaced by these newer rapid antigen detection and molecular-based methods. This review summarizes and discusses the availability, advantages, and disadvantages of molecular methods in the detection and identification of human gastrointestinal pathogens.